Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcell.2021.616887
|View full text |Cite|
|
Sign up to set email alerts
|

ENC1 Facilitates Colorectal Carcinoma Tumorigenesis and Metastasis via JAK2/STAT5/AKT Axis-Mediated Epithelial Mesenchymal Transition and Stemness

Abstract: Ectodermal neural cortex 1 (ENC1) is an actin-binding protein and has been known to be upregulated in several cancers, but the molecular mechanisms through which it contributes to the pathology of CRC have largely been elusive. We utilized data mining and validated the aberrant expression of ENC1, following which phenotypic traits of malignancy were assessed in vitro. Ruxolitinib was used as a surrogate to compare the effects of ENC1 expression and silencing on the JAK-STAT-AKT pathway. In vivo models were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…The overphosphorylation of STAT5 in the hyper-expressed JAK2/STAT5 pathway in mice has been found to result in a higher survival rate for prostate cancer, and hence has the possibility of being metastatic [ 109 ]. Similar findings were described by Cui and colleagues (2021) in mice with colorectal cancer [ 110 ]. Earlier, Chui and colleagues (2019) discovered that the activation of the JAK/STAT pathway occurs due to downregulation of TfR1 both in vivo and in vitro.…”
Section: Animal Model Of Metastatic Spread In Conjunction With Pathwayssupporting
confidence: 90%
“…The overphosphorylation of STAT5 in the hyper-expressed JAK2/STAT5 pathway in mice has been found to result in a higher survival rate for prostate cancer, and hence has the possibility of being metastatic [ 109 ]. Similar findings were described by Cui and colleagues (2021) in mice with colorectal cancer [ 110 ]. Earlier, Chui and colleagues (2019) discovered that the activation of the JAK/STAT pathway occurs due to downregulation of TfR1 both in vivo and in vitro.…”
Section: Animal Model Of Metastatic Spread In Conjunction With Pathwayssupporting
confidence: 90%
“…ENC1, an actin-binding protein that is essential for gastrulation and nerve formation ( Hernandez et al, 1997 ), has been reported to be overexpressed in the colon ( Cui et al, 2021 ), breast ( Zhou et al, 2020 ), and lung cancers ( Wu et al, 2021 ). A cohort study of TCGA dataset showed that overexpression of ENC1 is associated with tumor progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study of TCGA dataset showed that overexpression of ENC1 is associated with tumor progression and poor prognosis. Suppression of ENC1 expression inhibits the growth, migration and invasion of colon, breast, and lung cancer cell lines ( Cui et al, 2021 ; Wu et al, 2021 ; Zhou et al, 2020 ). Moreover, the knockdown of ENC1 significantly down-regulates the expression of mesenchymal markers (matrix metalloproteinase and N-cadherin) and up-regulates the expression of epithelial marker (E-cadherin) in lung cancer cell lines ( Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlighted some important pathways such as cytokine-cytokine receptor interaction, PI3K-Akt signaling pathway, and JAK-STAT signaling pathway targeted by biochanin A through the control of gene clusters ( CCND1, IL1A, IL2, KCND1 , and EGFR ). These pathways have been reported to be associated with immune responses in the lung and the carcinogenicity of CRC [ 41 , 42 ]. Cytokine-cytokine receptor interaction is responsible for the regulation of the tumor microenvironment and tumor cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%